Ikaros is a critical target during simultaneous exposure to X‐rays and N‐ethyl‐N‐nitrosourea in mouse T‐cell lymphomagenesis. Issue 2 (26th June 2012) - Hirano, Shinobu; Kakinuma, Shizuko; Amasaki, Yoshiko; Nishimura, Mayumi; Imaoka, Tatsuhiko; Fujimoto, Shinji; Hino, Okio; Shimada, Yoshiya
Abstract Cancer risk associated with radiation exposure is considered the result of concurrent exposure to other natural and manmade carcinogens. Available data on the molecular characteristics of cancer after simultaneous exposure to radiation and chemicals are insufficient. In our study, we used a mouse thymic lymphoma (TL) model that was synergistically induced by simultaneous exposure to X‐rays and N‐ethyl‐N‐nitrosourea (ENU) at subcarcinogenic doses and analyzed the mutation frequency and spectrum of the TL‐associated genes Ikaros, Notch1, p53 and Kras. We found that the point mutation frequency in Ikaros was significantly increased to 47% for simultaneous exposure compared to 13 and 0% for X‐ray and ENU exposure alone, respectively. These mutations were mostly G:C > A:T at non‐CpG sites and T:A > C:G, both of which are characteristic of ENU mutagenesis. About half of the point mutations were accompanied by loss of heterozygosity (LOH), typical of X‐irradiation. The remaining half did not include LOH, which suggests that they were dominant‐negative mutations. In Notch1, the frequency of abnormalities was high (>58%) regardless of the treatment, suggesting that Notch1 aberration may be important for T‐cell lymphomagenesis. The p53 and Kras mutation frequencies were low for all treatments (<23%). Importantly, the frequency of TLs containing mutations in multiple genes, especially both Ikaros and Notch1, increased after simultaneous exposure. Thus, after simultaneous exposure, Ikaros is a critical target and is inactivated by ENU‐induced point mutations and/or X‐ray‐induced LOH in T‐cell lymphomagenesis. Furthermore, concomitant alterations of multiple tumor‐associated genes may contribute to enhanced lymphomagenesis after simultaneous exposure.